2018
DOI: 10.1177/1744806918768972
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of therapeutic strategies for patients with radiculopathy: A network meta-analysis

Abstract: ObjectivesThe aim of this network meta-analysis is to assess the effectiveness of therapeutic strategies for patients with radiculopathy, including physical, medical, surgical, and other therapies.MethodsWe electronically searched electronic databases including PubMed and Embase for randomized controlled trials. The response rate and visual analog scale of pain change were considered as primary outcomes. The outcomes were measured by odds ratio (OR) value and corresponding 95% credible intervals (CrIs) or stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 41 publications
1
9
0
4
Order By: Relevance
“…Our results are in same direction of the systematic reviews of Cheng [ 41 ] and Zhang [ 39 ]. The first one [ 41 ] showed short-term results in favor of traction for the treatment of LBP with herniated intervertebral disks, but this review included studies on patients with and without LR.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results are in same direction of the systematic reviews of Cheng [ 41 ] and Zhang [ 39 ]. The first one [ 41 ] showed short-term results in favor of traction for the treatment of LBP with herniated intervertebral disks, but this review included studies on patients with and without LR.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, we conclude that the role of VT appears very limited in LR, since positive results were found only on pain and only when it was compared to medications or bed rest. Relative to the effects of medications in LR, there are conflicting conclusions on NSAIDs among who considered them as effective [ 8 ], who did not draw conclusions [ 6 ], and who did not recommend them [ 37 , 38 ], while a recent systematic review suggested that corticosteroids were effective in LR [ 39 ]. Concerning the advice of bed rest or stay active in patients with sciatica, little or no difference emerged on pain and function, with moderate quality evidence [ 6 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is because the traditional pairwise meta‐analysis can only achieve direct comparison between the two interventions and cannot comprehensively evaluate the efficacy of various interventions. Network meta‐analysis is an extension of traditional pairwise meta‐analysis to multiple treatment comparisons and is a good choice when there is a lack of direct evidence, because it allows indirect comparisons between different types of treatment …”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Network meta-analysis is an extension of traditional pairwise meta-analysis to multiple treatment comparisons and is a good choice when there is a lack of direct evidence, because it allows indirect comparisons between different types of treatment. 29,30 Therefore, this study used Bayesian network meta-analysis to systematically evaluate the efficacy of CHIs for the treatment of mycoplasma pneumonia in children and obtain the ranking of their effect in different outcomes, to provide evidence of evidence-based medicine for the clinicians to choose a more suitable therapy.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…Available treatment options are broadly divided into pharmacologic, conservative, interventional and surgical (2). The Guidelines from the American Pain Society highlight that the risk-benefit analysis of invasive therapies in this condition is controversial and therefore, advises that it is more reasonable to first consider conservative management that focuses on appropriate pain control and functional recovery (3).…”
mentioning
confidence: 99%